Assessment of the impacts of an oil spill on the populations of common guillemot (Uria aalge) and long-tailed duck (Clangula hyemalis) - an expert knowledge based Bayesian network for the Gulf of Finland - Venesjärvi, Riikka (2012)
The amount of operated oil transports continues to increase in the Gulf of Finland and in the case of an accident hazardous amounts of oil may be spilled into the sea. The oil accident may be harmful for the common guillemot and long-tailed duck populations. In this study expert knowledge regarding the behaviour and population dynamics of common guillemot and long-tailed duck in the Gulf of Finland was used to build a model to assess the impacts of an oil spill on the mortality and population size of these species. The Bayesian networks were used in the modelling. Based on the results the breeding colony of guillemots in Aspskär may survive in the consequence of recolonization. In conclusion, sufficient cleaning of the breeding site is important. The loss of one year offspring production may not have severe impact on the population size, the survival of adult breeders is more significant. The Baltic Sea population of long-tailed duck suffer from high nesting mortality at the breeding sites in the Northern Arctic Ocean. Thus the population has low offspring production; in the lack of chicks the possible oil spill may be directed only to adult breeders. The loss of experienced breeders during their migration may be harmful for the population. The models of common guillemot and long-tailed duck created and their results may be utilized in later oil impact studies on sensitive species.